Digital multicriteria evaluation of negotiated medicines using Chinese mini-HTA: application of structured methodologies in assessing once-weekly GLP-1 RAs for improved clinical decision-making - Li, Xiao; Qiu, Zhihong; Xue, Chaojun; Ren, Xiaokai; Dong, Zhanjun (Frontiers in Pharmacology, 2025)
BackgroundSystematic and transparent evaluation of medicines remains a global challenge. In China, structured frameworks for clinical value assessment are underutilized despite improved access to negotiated medicines. Once-weekly glucagon-like peptide-1 receptor agonists (GLP-1 RAs) were selected as a representative case for their reimbursement status and clinical and economic relevance. This study applied a quantitative mini-health (mini-HTA) technology assessment to support rational drug selection.1MethodsA structured, three-stage methodology was employed to evaluate four once-weekly GLP-1 RAs. First, a weighted scoring system was established for five dimensions—pharmaceutical properties, effectiveness, safety, economy, and other considerations—based on expert consensus using the Quantitative Record Form for Drug Evaluation and Selection in Medical Institutions. Second, evidence for each dimension was systematically collected using a PICO-based search strategy across guideline databases, literature sources, and official documents. Third, each drug was quantitatively scored in each dimension according to predefined criteria and expert-assigned weights; the total scores were used to classify drugs into recommendation levels (“strongly recommended,” “weakly recommended,” or “not recommended”) to guide evidence-based selection in medical institutions.ResultsSemaglutide (77.8) and dulaglutide (76.3) achieved the highest totals, driven by superior HbA1c reduction and proven cardiovascular benefit, and were strongly recommended. Exenatide microspheres scored 70.2, mainly owing to favourable acquisition cost, and was also strongly recommended. PEG loxenatide scored 62.9, limited by narrower reimbursement coverage and lower international uptake, and received a weak recommendation. Safety profiles were comparable across agents.ConclusionThe study demonstrates that a structured, expert-informed mini-HTA framework can be feasibly applied for quantitative evaluation and selection of once-weekly GLP-1 RAs in Chinese medical institutions. Key differentiators among agents were efficacy (notably cardiovascular benefit) and economic/policy factors, while safety differences were minimal. This replicable approach improves transparency, consistency, and evidence-based decision-making in clinical pharmacy and institutional formulary management.